The Fabelmans [videorecording (Blu-Ray + DVD)] - Williams, John, 1932- (Universal, 2023)
Young Sammy Fabelman falls in love with movies after his parents take him to see "The Greatest Show on Earth". Armed with a camera, Sammy starts to make his films at home, much to the delight of his supportive mother although his practical father has doubts.